A new two-mode fluorescence signal amplification strategy for protease activity assay based on graphene oxide. Issue 76 (12th October 2017) - Wang, Fangfang; Gao, Jie; Zhao, Jianwei; Zhang, Wenyue; Bai, Jie; Jia, Hongxia; Wang, Yucong
Abstract : A new graphene oxide-based two-mode fluorescence signal amplification strategy for the detection of protease activity has been established. Abstract : A graphene oxide (GO)-based two-mode fluorescence signal amplification assay of protease activity has been established. GO can adsorb the FITC-labeled substrate peptide and quench the fluorescence of FITC. In the presence of the target protein, carboxypeptidase Y (CPY), the FITC-labeled substrate peptide is hydrolyzed by CPY, leading to the turn-on of fluorescence. The fluorescence intensity increases significantly after the hydrolysis. More interestingly, it is even much higher than the fluorescence intensity of the added FITC-labeled substrate peptides. It is deduced that the extraordinary growing of fluorescence intensity is attributed to the hydrolysis also. The strong quenching efficiency of GO significantly improved the signal-to-noise ratio (SNR) of the proposed method for protease analysis. By combining the GO-based fluorescence turn-on with the fluorescence signal amplification induced by hydrolysis, the proposed method obtained higher sensitivity and specificity for CPY activity detection. The detection limit for CPY activity assay is estimated to be 1.0 × 10 −5 U μL −1 . The other proteins, proteases and a complicated matrix cannot disturb the assay of CPY activity.